Redes y estrategias de ascenso en la Monarquía Hispánica. La familia Malvezzi y el Colegio de España en Bolonia (siglos XV-XVI) - López-Guadalupe Pallarés, Miguel José (Historia de las Universidades, 2023)
This book analyses the social relations between the Malvezzi lineage and the College of Spain in Bologna. The apparently strange symbiosis between a family of the urban oligarchy and a secular university college can be explained in the context of the creation of factions favourable to the Houses of Austria and Valois, which polarised Italian political life. Thus, the college, which participated in the administrative structures of the monarchy, became part of a Hispanophile circuit created in Bologna and led by the Malvezzi family. The aim of these affinity networks was the social promotion of their male leaders through political and military service to the Spanish monarchs. From the precedents in the kingdom of Naples, we move on to the articulation of a philo-Habsburg party in Bologna that extended its influence beyond the city, and which counted on the College of Spain and several of its collegiates throughout the 16th century. In this way, the foundations of the Malvezzi's local power are integrated into the Italian philo-Spanish networks, combining the urban, regional and international scales. A study that relies on Network Analysis in order to properly interpret the involvement of the college and the personal interests of each of the Italian leaders involved. Finally, it addresses questions related to symbolic capital, attempting to unravel the fundamental points of the hispanophilic narrative elaborated by the Malvezzi family and the collaboration of the College of Spain in this ideological enterprise. This contribution not only broadens our knowledge of the phenomenon of philo-Spanish factions in Renaissance Italy, but also allows us to interpret the role played by a university college in a city where, unlike Rome, Naples or Milan, there were no centres of reference for the Spanish Monarchy.